Nitrogen removal by a strengthened comprehensive floating bed with embedded pellets made by a newly isolated Pseudomonas sp. Y1 - Cheng, Wanyun (Environmental technology, 2024)
A newly heterotrophic nitrification aerobic denitrification(HN-AD) bacterium Pseudomonas sp. Y1 with highly nitrogen removal ability was isolated from the activated sludge, TN removal rate of which was 99.73%. In this study, two types of different ecology floating bed systems were designed to achieve efficient nitrogen removal in the urban eutrophic landscape water body, one is the comprehensive ecological floating bed(CEFB) system with only Lythrum salicari and the other is the strengthened comprehensive ecological floating bed (SCEFB) system with both Lythrum and embedded pellets made by Y1. The TN removal rates of the CEFB system were 33.82%, 83.84% and 88.91% at 8±1℃, 15±1℃ and 25±1℃, respectively, while the TN removal rates of the SCEFB system increased by nearly 40%, 16% and 11% at the same environment, respectively. The result shows that the SCEFB system can purify the simulated water from surface water body class V to class IV. Thus it has a broad application prospect in the urban eutrophic landscape water body